2017
DOI: 10.3855/jidc.8056
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of subclinical peripheral neuropathy in cases of untreated brucellosis

Abstract: Introduction: Brucellosis is a common zoonotic disease in some areas of the world. It may affect several organs and is known to involve the nervous system in 2.7-17.8% of affected patients. During the progression of brucellosis, peripheral neuropathies (PNs) have been reported. However, there are few studies investigating the presence of subclinical neuropathy in asymptomatic patients. In our study, we aimed to evaluate the presence of peripheral neuropathy using electrophysiological methods in newly-diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…7 Nervous system involvement has been reported between 2.7% and 17.8% in brucellosis cases. 5 In their study including 60 brucellosis patients, Sanivar et al 5 found impairment in EMG in all patients and claimed that brucellosis may effect on the nervous system, including clinical or subclinical peripheral neuropathy. Although the prevalence of optic nerve involvement was reported as 10% in brucellosis cases, these reports are generally in the form of case reports in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 Nervous system involvement has been reported between 2.7% and 17.8% in brucellosis cases. 5 In their study including 60 brucellosis patients, Sanivar et al 5 found impairment in EMG in all patients and claimed that brucellosis may effect on the nervous system, including clinical or subclinical peripheral neuropathy. Although the prevalence of optic nerve involvement was reported as 10% in brucellosis cases, these reports are generally in the form of case reports in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…3 Although optic neuritis cases due to brucellosis were reported less frequently, nervous system involvement has been reported to occur between 2.7% and 17.8% of brucellosis patients in general. 5 Moreover, electromyography (EMG) studies have shown that subclinical peripheral neuropathy can also be observed in brucellosis. 6 To investigate if there is microinvasive involvement in the optic nerve and choroid due to brucellosis, we evaluated choroidal thickness and retinal nerve fiber layer (RNFL) analysis in patients with brucellosis in the acute stage.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral changes 60% [29] Meningitis 50% [18] Peripheral neuropathy 18--35.2% [33,34] Cranial neuropathies 19% [16] Myelopathy 5--17% [16,31,32] Cerebrovascular complications 16% [23] Seizures 3--11% [16,19 mycotic aneurysms or thrombotic obliteration or septic emboli from endocarditis [16,24,25]. Most importantly, brucellosis should be considered in the differential diagnosis of acute vascular lesions in endemic areas [16].…”
Section: Neurological Complications Prevalencementioning
confidence: 99%
“…Whether the cause is an immune process or a cytokine storm, ultimately COVID-19 can affect the peripheral nervous system. Subclinical peripheral nervous system involvement can be seen in some chronic diseases or infectious diseases 7,8 . Subclinical involvement of peripheral nerves can be described as abnormality in nerve conduction studies without symptoms associated with peripheral nervous system involvement 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical peripheral nervous system involvement can be seen in some chronic diseases or infectious diseases 7,8 . Subclinical involvement of peripheral nerves can be described as abnormality in nerve conduction studies without symptoms associated with peripheral nervous system involvement 7,8 . Subclinical peripheral nervous system involvement can be demonstrated by nerve conduction studies.…”
Section: Introductionmentioning
confidence: 99%